Metode Mengajar dalam Pendidikan Menurut Nur Uhbiyati dan E. Mulyasa - M. Ilyas; Armizi Armizi (Al-Liqo: Jurnal Pendidikan Islam, 2020)
The learning method is a strategy or technique in delivering teaching and learning activities in the classroom that is applied by teachers so that the set of goals can be achieved objectively. The learning process requires a variety of special methods which in essence can support the achievement of effective and efficient learning objectives. Teachers need to know and learn appropriate teaching methods to convey material to students. Teaching methods are practiced at the time of teaching and made as attractive as possible so that students can receive lessons easier. Additionally, the teacher must also know the advantages and disadvantages of the methods to reduce difficulties during teaching and learning. This research was formulated using the method by Nur Uhbiyati and E. Mulyasa.